Feminisme Sosialis: Gerakan Clara Zetkin dalam Perjuangan Identitas dan Kelas Perempuan di Jerman 1891-1917 - Meylawati, Nur Insani; Supriatna, Nana; Darmawan, Wawan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This research aims to conduct an in-depth study of the role of Clara Zetkin and the women’s movement in Germany. The main problem raised in this study is “How was Clara Zetkin’s struggle in the socialist women’s movement in Germany?” The research used the historical method through four stages: heuristics, criticism, interpretation, and historiography. For a more profound analysis, this research uses three theories: socialism, feminism, and social movement. Zetkin also combined feminist and socialist ideas in her movement. She brought the feminist-socialist idea as a weapon against capitalism that oppressed women, and she was not only focused on the gender issues but also on the social class problems. In her struggle, Zetkin used Die Gleichheit as a platform to educate female workers so that they could participate in the class struggle that led to the liberation of women.